Surgical Fear and Related Factors Before Total Knee Arthroplasty - Esra Kuşçu; Aliye Okgün Alcan (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: The aim of this descriptive study was to determine the level of surgical fear and related factors in patients undergoing total knee arthroplasty.Methods: The study sample consisted of 181 patients undergoing total knee arthroplasty in a training and research hospital in Izmir. The data were collected between April 1 and September 1, 2023 via the “Patient Identification Form” and the “Surgical Fear Scale”. Descriptive statistics, Mann Whitney U test, Kruskal Wallis test and Spearman correlation analysis were used to evaluate the data.Results: The mean score on the Surgical Fear Scale was found to be 28.35 ± 16.89 (out of 80 points), indicating that the level of fear experienced by patients scheduled for total knee arthroplasty was relatively low. The mean scores for the short-term and long-term fear subscale of the Surgical Fear Scale (16.10 ± 9.91 and 12.24 ± 9.44 out of 40, respectively) also indicated that the short-term and long-term fear levels were low. The factors associated with the level of surgical fear were found to be previous knee surgery history and type of anesthesia (p: .001).Conclusion: The study findings showed that patients undergoing total knee arthroplasty experienced low levels of fear and that previous knee surgery experience and type of anesthesia were associated with this fear. surgical fear levels.